A comprehensive study of large negative dispersion and highly nonlinear perforated core PCF: theoretical insight. (1st June 2022) - Singh, Shivam; Upadhyay, Anurag; Sharma, Divya; Taya, Sofyan A
Abstract: A photonic crystal fiber (PCF) containing circularly organized square-shaped air holes in the cladding region is investigated. The fiber core is perforated with four circular air-filled holes to instate high nonlinearity and large negative dispersion. The numerical analysis is done with a finite element method based COMSOL Multiphysics tool to investigate different optical properties of the propounded PCF. The simulation outcome verifies a high nonlinear coefficient value of 85 W −1 Km −1 at telecommunication window 1.55 μ m which is, the highest ever achieved value on comparing with the other existing literature without using any nonlinear materials or liquids to the best of the authors' knowledge. In parallel, the large negative value of dispersion −597 ps nm −1 km −1 is achieved for S/Λ equals 0.70 at the same communication window. However, the highest achieved nonlinearity and negative dispersion are 300 W −1 Km −1 and −1689 ps/nm/km. Moreover, birefringence, numerical aperture, and propagation loss are also measured as 2.40 × 10 −3, 0.59, and 4.12 × 10 −11 dB m −1 respectively along with an extremely high core power fraction of 99.98%. Hence, the propounded PCF is suitable for residual dispersion compensation, supercontinuum generation, and high bitrate transmission.